Fibromyalgia in the mothers of the children with cerebral palsy, and determination of the related depression and anxiety situations - Toy, Şeyma; Beykumül, Ayşegül; Avcı, Zeynep Tuğçe; Büyükavcı, Raikan (The European Research Journal, 2019)
Objectives: In this study, it was aimed to evaluate maternal functional status, quality of life, depression and anxiety measurements according to the child's functional level in the mothers, who were diagnosed with fibromyalgia syndrome (FMS), of children with cerebral palsy (CP).Methods: Ninety-seven mothers diagnosed with FMS, whose children had CP, were included in the study. Children with CP were divided into two functional levels with the Gross Motor Function Classification System (GMFCS) as mild-moderate (level 1, 2 and 3) and severe (level 4 and 5). On mothers, The Fibromyalgia Impact Questionnaire (FIQ) was used to assess the functional levels and quality of life, Beck Depression Inventory (BDI) was used to evaluate the depression level, and Beck Anxiety Inventory (BAI) was used to determine the anxiety level.Results: The mean age of the 97 female patients participating in the study was 35.93 ± 8.72 years. According to GMFCS, 67% of children with CP were mild to moderate while 33% were severe. There was a significant positive correlation between GMFCS levels of children with CP and their mother's FIQ, BDI, and BAI scores (p < 0.05). Conclusions: Maintaining the daily life of a child with CP is a parenting-focused situation. Especially it affects the mother physically and mentally. Our study suggests that the severe physical condition of the child with CP increases the mother's FIQ, depression, and anxiety. It has been determined that studies on CP should not ignore the parental factor as well as research on the disease itself.